Creation of Exotic Dramatic Fashion with the Source Idea of Barong Ider Bumi - Rahmawati, Efi; Nahari, Inty; Arifiana, Deny; Mayasari, Peppy (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
Barong Ider Bumi is a ritual tradition to ward off disaster for the Osing community located in Kemiren Village, Glagah District, Banyuwangi. The uniqueness of the Barong Osing form which contains philosophical meaning is the basis for the inspiration for the creation of exotic dramatic clothing. Forms based on oriental aesthetics and sensibilities inspire the combination of clothing into an exotic dramatic style to display traditional elements that are packaged in a modern way to have a different style that shows a comprehensive visual representation of strength and intensity. This study of creative practice aims to describe the process of creating exotic dramatic clothing with Barong Ider Bumi as its inspiration. The method used is Practice-Ied Research, namely research based on the practice of the creative process by Hendriyana (2021) which consists of four stages including: (1) the exploration stage related to the exploration of information on sources of ideas, (2) the design stage in the form of making sketch designs, (3) the embodiment as the process of realizing the selected design and evaluation, and (4) the presentation stage of the work. The result of this creation is three exotic dramatic outfits consisting of one men's outfit and two women's outfits that will be presented at the 35th annual fashion show "Jagad Osing".